2015
DOI: 10.1016/j.devcel.2015.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol-Phosphatidic Acid Exchange by Nir2 at ER-PM Contact Sites Maintains Phosphoinositide Signaling Competence

Abstract: SUMMARY Sustained agonist-induced production of the second messengers InsP3 and diacylglycerol requires steady delivery of phosphatidylinositol (PtdIns) from its site of synthesis in the ER to the plasma membrane (PM) to maintain PtdIns(4,5)P2 levels. Similarly, phosphatidic acid (PtdOH), generated from diacylglycerol in the PM, has to reach the ER for PtdIns resynthesis. Here, we show that the Drosophila RdgB homolog, Nir2, a presumed PtdIns transfer protein, not only transfers PtdIns from the ER to the PM bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
287
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(299 citation statements)
references
References 42 publications
8
287
1
3
Order By: Relevance
“…The evolution of a single protein with dual (PI/PA) transfer activities offers an elegant solution to the need to move two distinct lipids between cellular compartments to maintain the PI(4,5)P 2 cycle. Conceptually similar findings were reported in a study performed on the human orthologue of RDGBα, PITPNM1 in mammalian cells [32]. These authors found that intact PITPNM1 function was required to remove PA from the PM and restore PI(4,5)P 2 levels during stimulation of mammalian cells with agonists that stimulate G-protein-coupled PLC activity; thus PITPNM1 was required to regulate PA and PI homoeostasis during PLC signalling.…”
Section: Proposed Functions Of the Sub-microvillar Cisternaesupporting
confidence: 60%
“…The evolution of a single protein with dual (PI/PA) transfer activities offers an elegant solution to the need to move two distinct lipids between cellular compartments to maintain the PI(4,5)P 2 cycle. Conceptually similar findings were reported in a study performed on the human orthologue of RDGBα, PITPNM1 in mammalian cells [32]. These authors found that intact PITPNM1 function was required to remove PA from the PM and restore PI(4,5)P 2 levels during stimulation of mammalian cells with agonists that stimulate G-protein-coupled PLC activity; thus PITPNM1 was required to regulate PA and PI homoeostasis during PLC signalling.…”
Section: Proposed Functions Of the Sub-microvillar Cisternaesupporting
confidence: 60%
“…The tricalbins found in yeast are structurally and functionally homologous to E-Syts [42,43]. Following phospholipase C (PLC)-activating stimuli, Nir2 is recruited to ER-PM contact sites, where it transfers phosphatidic acid (PA) generated in the PM to the ER [44]. The relocation of Nir2 involves VAP in the ER and PA in the PM.…”
Section: Er-pm Contact Sitesmentioning
confidence: 99%
“…This led to a proposal that the role of septins at the bud neck might therefore be to scaffold the formation of ER-plasma membrane contact sites to control the production and/or delivery of specific lipids to these domains [44]. Support for this notion comes from a recent report revealing localisation of a phosphatidylinositol/phosphatidic acid exchange protein at ER-plasma membrane contact sites [45]; this exciting observation suggests that these specific domains may serve as a focal point for the modulation of plasma membrane lipid composition. We shall return to this issue in section 5.…”
Section: Ist2p -An Er-based Microdomain At the Bud Neck?mentioning
confidence: 74%
“…The localisation of ER to the bud neck might represent a distinct means of delivering specific lipid species into the abscission zone [42], a notion given credence by the specific localisation of phosphatidylinositol/ phosphatidic acid exchange proteins at these sites [45]; relatives of this protein could be responsible for the midbody-specific localisation of phosphatidic acid and phosphoinositides.…”
Section: The Lipid Composition Of the Midbody Is Distinctmentioning
confidence: 99%